The role of government in the attraction and utilisation of FDI: The case of Northern Ireland - Crean, Michael (2008)
This dissertation is submitted in part for the MSc International Business. It is a study into the role of government in the attraction and utilisation of FDI. The author uses a comparative study approach focusing on the case of Northern Ireland and attempts by the goverment to grow the economy through FDI and the experience of the Republic of Ireland's successful economic boom in the 1990s. The literature review is in two parts; part 1 focuses on the scholarly literature around the role of government in the attraction and utilisation of FDI, part 2 focuses on the factors that explain the economic boom in the Republic of Ireland in the 1990s. The purpose of the literature review is to inform the research and analysis when it is applied to the case of Northern Ireland. The research approach is qualitative using secondary research taken from scholarly articles and government publications. The secondary literature is supplemented by a series of in-depth interviews used to inform the literature. The research focuses around three key questions that relate to the various strengths and weaknesses of Northern Ireland as a location for FDI, the similarities and differences between the experiences of Northern Ireland and the Republic of Ireland and the lessons that can be taken from the experience of the Republic of Ireland and applied to Northern Ireland. The study leads to a number of conclusions and suggests a number of areas in which the study can be extended.